O imaginário coletivo de estudantes de psicologia sobre distúrbios psicossomáticos - Volpato, Ana Lúcia [UNESP] (2014)
The unconscious psychological fields are organizations that influence intersubjective practices, both individual and collective. Thus, the study of the collective imagination of psychologists in training is very important, as this can interfere with their therapeutic practices. The objective of this research is investigate the collective imagination of students of fourth and fifth years of Psychology at UNESP / Assis - they were acting on stage nuclei in psychoanalytic clinic in Winnicott's approach - regarding psychosomatic disorders. The research involved the participation of 8 students, by using the procedure of Drawing-Story with Theme. Instructions for the application was: Draw a person with psychosomatic disorder. This instrument was applied through a group interview for the collective imaginary approach, which provided the possibility of survey participants get in touch and share feelings about the topic covered. After using this tool, we analyze some psychological fields and subfields of the collective imagination that emerged from productions such as the field of Feelings and the subfield of Loneliness. These fields and subfields were the object of Winnicott's psychoanalytic analysis. From our analysis, we observed that students have a basic understanding of Winnicott's theory. However, regarding the psychosomatic, his views also demonstrated restrictions. Although this has been observed, the productions have shown the value of the topics brought by them as well as the importance of other works that address these issues